1984
DOI: 10.1002/j.1460-2075.1984.tb01816.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the human c-myc locus: provocative open reading frame within the first exon.

Abstract: The nucleotide sequence of a HindIII‐EcoRI DNA fragment, 8 kbp long, of a lambda recombinant containing the whole human c‐myc gene has been deduced by the method of Maxam and Gilbert. This fragment encodes the complex c‐myc locus and the sequence provides information relative to the 2.7 kb long c‐myc transcript. It appears that although exons 2 and 3 would code for a 48‐K protein homologous to the myc domain of the viral p110 gag‐myc protein, the first exon, which has a large open reading frame ending with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(121 citation statements)
references
References 32 publications
3
118
0
Order By: Relevance
“…In order to quantify and to localize more precisely the new site induced in c-myc, the autoradiogram shown in [22]. The analysis also indicated that the intensity of cleavage induced by mAMSA at position +3100 was equal to 19.5% and 3.5% of the total c-myc gene cleavage generated for differentiated or undifferentiated HL60 cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In order to quantify and to localize more precisely the new site induced in c-myc, the autoradiogram shown in [22]. The analysis also indicated that the intensity of cleavage induced by mAMSA at position +3100 was equal to 19.5% and 3.5% of the total c-myc gene cleavage generated for differentiated or undifferentiated HL60 cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The hTIC-myc plasmid was generated by sticky and blunt end ligation, respectively, of the hTIC XbaI and SphI sites to a 4575 bp XbaI/EcoRI gene fragment of the human c-myc gene. This fragment spans nt 3507-8082 (Gazin et al, 1984) and includes the complete c-myc exon 2/3 region and second intron with the preferred ATG start codon in exon 2, plus a portion of intron one. It does not contain the weak alternative translation start site found in exon 1 (Gazin et al, 1984) and only p62 Myc protein can be produced.…”
Section: Generation Of Rodent ®Broblast Cell Lines Stably Transfectedmentioning
confidence: 99%
“…This fragment spans nt 3507-8082 (Gazin et al, 1984) and includes the complete c-myc exon 2/3 region and second intron with the preferred ATG start codon in exon 2, plus a portion of intron one. It does not contain the weak alternative translation start site found in exon 1 (Gazin et al, 1984) and only p62 Myc protein can be produced. The hTIC-myc plasmid was linearized at a unique FspI restriction enzyme site before transfection.…”
Section: Generation Of Rodent ®Broblast Cell Lines Stably Transfectedmentioning
confidence: 99%
See 2 more Smart Citations